A return to lived experiencers themselves: Participatory action research of and by psychosocial clubhouse members - Lester Vescey; Jennifer Yoon; Kevin Rice; Members of PARCO Group; Larry Davidson; Miraj Desai (Frontiers in Psychology, 2023)
IntroductionWithin the history of psychology and phenomenology, people with lived experience of mental illness have often served as participants in research, but far less as co-researchers themselves. There is now a growing movement focused on “participatory” research, where people with lived experience directly contribute to various stages of the research process. This article presents such a qualitative, participatory research study, led by members of a large psychosocial rehabilitation clubhouse—Fountain House in New York City—and informed by phenomenological research principles. The study focused on collaboratively assessing and improving the clubhouse program for its members.MethodsA key feature of the project was the extent of lived experiencer involvement, for instance, in designing and conducting the study, and co-writing this research report. Members of Fountain House were trained in phenomenologically-informed research methods and developed a research study that focused on the quality improvement of their clubhouse program. Member researchers conducted a series of focus groups with fellow clubhouse members, generating qualitative data that were analyzed and written up by member researchers in collaboration with staff and university partners.ResultsOverall, study findings place emphasis on the theme of action in members’ experiences—both with respect to how action, agency, and valued activity were key drivers of meaning and recovery for people facing severe mental illness, and with respect to the key component of the research process itself [i.e., participatory action research (PAR)]. Four major subthemes emerged from the study. First, findings revealed how members with mental illness experienced the clubhouse as a “new hope” and “the place for me,” to counteract their experience of inactivity, stigma, depression, and hopelessness prior to that point. Second, findings showed how, as members’ life goals changed, so did the precise meaning and role of Fountain House in their lives. Third, findings portrayed members’ need for, and pursuit of, transformation within the clubhouse space itself to provide more opportunities for meaningful work rather than what they viewed as merely busy-work. Finally, member researchers viewed their direct participation in this project as an opportunity to actively combat stigma, to be a driver of research, and to engage in what they viewed as a generative activity.DiscussionThese action-oriented themes serve as a counter to the historical view of people with mental illness as merely passive experiencers of symptoms and passive recipients of mental health care. We discuss how the process and content of participatory research can help enhance the relevance of research for stakeholders’ lives and contexts.